Research on real-world emission characteristics based on the Symmetry Solid SCR system - Yingshuai Liu; Jianwei Tan; Chenxing Liu; Yunli He (PLoS ONE, 2025)
In the actual use process, especially under the low exhaust temperature in urban conditions, the actual NOx emission of diesel engines using the Urea SCR technology is higher than expected, which seriously affects the application of Urea SCR technology in urban diesel vehicles. To solve the defects of low-temperature freezing, urea crystallization in the exhaust pipeline at low exhaust temperature, and insufficient activity of the Urea SCR system at low exhaust temperature in the actual application process of the Urea SCR technology, this paper uses the Portable Emission Measurement System (PEMS) vehicle test system to run the real-world. A SAIC Hongyan Dump truck that meets the China VI emission standard is tested and studied, and the real-world emission characteristics of the Solid SCR system and the Urea SCR system are compared and studied. Among other things, solid-state SCR systems use solid ammonium as a precursor to ammonia, a change that reduces clogging problems due to icing and hydrolysis evaporation crystals at low temperatures compared to conventional aqueous urea solutions. This results in more reliable system operation in cold environments. Solid-state SCR technology offers a more efficient and reliable solution for diesel exhaust treatment through its unique ammonia supply method, system optimization and environmental adaptability, helping to reduce environmental pollution from diesel vehicles. The test results show that: Under real-world operation conditions, the NOx conversion efficiency of the Urea SCR system and the Solid SCR system with the same injection strategy is increased by 0.5% and the NOx emission is reduced by 8.9% when the window average temperature is 228.8°C and 231.3°C. For the PN emission, no matter whether the Urea SCR system or the Solid SCR system is selected, the results have little influence. Based on the Solid SCR system, CO, HC, NO, NOX, and other pollutant emission factors gradually decrease and tend to be relatively stable with the increase in vehicle speed. The Solid SCR technology is a promising NOx emission control technology for diesel engines.